2019
DOI: 10.1042/bcj20190251
|View full text |Cite
|
Sign up to set email alerts
|

A novel small molecule A2A adenosine receptor agonist, indirubin-3′-monoxime, alleviates lipid-induced inflammation and insulin resistance in 3T3-L1 adipocytes

Abstract: Saturated free fatty acid-induced adipocyte inflammation plays a pivotal role in implementing insulin resistance and type 2 diabetes. Recent reports suggest A2A adenosine receptor (A2AAR) could be an attractive choice to counteract adipocyte inflammation and insulin resistance. Thus, an effective A2AAR agonist devoid of any toxicity is highly appealing. Here, we report that indirubin-3′-monoxime (I3M), a derivative of the bisindole alkaloid indirubin, efficiently binds and activates A2AAR which leads to the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…In the preparation of ligands, the structures of phytochemicals detected through the GC-MS technique from the methanolic leaf extract were retrieved from the PubChem database ( Choudhary et al, 2019 ) in SDF format. Afterward, the Avogadro software was used to optimize the geometry of the phytochemicals ( Snyder and Kucukkal, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the preparation of ligands, the structures of phytochemicals detected through the GC-MS technique from the methanolic leaf extract were retrieved from the PubChem database ( Choudhary et al, 2019 ) in SDF format. Afterward, the Avogadro software was used to optimize the geometry of the phytochemicals ( Snyder and Kucukkal, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Using a combination of in silico virtual screening of potential anti-diabetic candidates and an in vitro study using an insulin-resistant model of 3T3-L1 adipocytes, Choudhary et al [ 106 ] showed that 1 prevented lipid-induced impairment of the insulin signaling pathway in adipocytes via A2A adenosine receptor activation. While compound 1 reduced lipid-induced adipocyte inflammation by inhibiting NF-κB dependent pro-inflammatory cytokine expression, it also augmented cAMP responsive element binding protein (CREB) activation, favoring an overall anti-inflammatory state [ 106 ].…”
Section: Indirubin Oxime-based Kinase Inhibitorsmentioning
confidence: 99%
“…AutoDock and AutoDockFR to get optimal receptor-ligand conformations. From the 142 compounds finally we got one molecule "indirubin-3′-monoxime" which is then followed by experimental validations [75].…”
Section: Application Examples Of Molecular Dockingmentioning
confidence: 99%